Seasonal variation in weed seedbank in the rice field soils of Muda Area, Peninsular Malaysia - S.M. Rezaul Karim; Mashhor Mansor; Zainal Abidin Abd Hamid (2012)
An investigation was carried out at the Muda rice fields, Peninsular Malaysia during four consecutive seasons of 2004 and 2005 to study the seasonal variation in the weed seedbank. Species composition with their dominance ranking and similarity between the species were recorded. A total of 577 seeds/sample (3337 seeds/m ) in 1/2004, 970 seeds/sample (5659 seeds/m ) in 2/2004, 928 seeds/sample (5384 seeds/m ) in 1/2005 2 2 2 and 471 seeds/sample (2722 seeds/m ) were recorded in the season 2/2005. Time taken to emerge the whole 2 seedbank varied from 44 to 72 weeks. Eight weed species namely, Fimbristylis miliacea,. Ludwigia. hyssopifolia, Oryza sativa complex (weedy rice), Scirpus grossus, Echinochloa crusgalli, Sagittaria guyanensis, Scirpus juncoides and Ischaemum rugosum were found to emerge from the seedbank. The species F. miliacea, L. Hyssopifolia and O. sativa contributed more than 80% of the total weed population. Among the weed species, F. miliacea and L. hyssopifolia are grouped, E. crusgalli, S. guyanensis and S. grossus are grouped and S. juncoides and I. rugosum are grouped together due to their similar frequencies of occurrence within the respective groups. Among the seasons of study, 1/2005 and 2/2005 were most similar with high value of similarity index (0.981).